ABOUT THE SYSTEM OF PRACTICE-ORIENTED SCIENTIFIC AND TECHNICAL CREATIVITY - A. A. Maltseva; N. E. Barsukova; E. V. Klyushnikova (Высшее образование в России)
The paper focuses on studying and systematization ofthe activity ofeducational institutions in the field ofcreation and development the system of practice-oriented scientific and technical creativity of students and pupils in engineering fields. The scientific and educational environment of universities in general was chosen as the object of study. The purpose of the analysis was to identify all types of structural units and the communities of enthusiasts, which contribute to the development of scientific and technical creativity of the youth and the development of engineering education. The article analyzes such aspects as the university structures, which provide the base for scientific and technical clubs, the target audience of students, system of curators, areas of activity, forms and methods of work, types used in club activities. The analysis was performed on the results of the monitoring of their activity, which was for the first time held in the framework of the project "Development and implementation ofthe method for improvement the efficiency ofactivity ofpractice-oriented scientific and technical clubs of creative development of students and pupils."